Dendrophthoe pentandra Induced Apoptosis and Cell Cycle Arrest at G1/S in Human Breast Adenocarcinoma Cells, MCF-7 via Up- Regulation of p53 - Nik Aina Syazana Nik Zainuddin,Yusmazura Zakaria,Mohd Dasuki Sul’ain (Journal of Applied Pharmaceutical Science, 2018)
D. pentandra is a semi-parasitic plant with traditional claim of having antiproliferative and anticancer properties. However, the mechanism underlying anticancer activity of this plant remains unclear. This study aims to evaluate the antiproliferative activity of D. pentandra and its mechanism of action in cancer treatment. The extraction of D. pentandra was performed using methanol. The antiproliferative activity of D. pentandra methanol extract using MTT Assay showed inhibition on MCF-7 cell proliferation with IC50 of 10.65 ± 0.49 μg/ml. Hoechst 33258 nuclear staining displayed chromatin condensation, fragmented nuclei, and formation of apoptotic bodies upon treatment with IC50 of D. pentandra methanol extract. Mechanism of cell death in D. pentandra methanol extract-treated MCF-7 cells were performed by flow cytometric analysis. The analysis confirmed that D. pentandra methanol extract-treated MCF-7 arrested cell cycle distribution at the G1/S phase and induced apoptosis using AnnexinV/propidium iodide double staining. The mechanism of action was further confirmed by determination of protein involved in apoptosis pathway; Bcl-2, Bax, and p53. The findings suggested that the increased p53 was followed by an increase of pro-apoptotic Bax and decrease of anti-apoptotic Bcl-2 that led to apoptosis. In conclusion, the anticancer effect of D. pentandra methanol extract against MCF-7 cells by induction of apoptotic cell death is a promising approach for breast cancer treatment..
Keywords: Dendrophthoe pentandra,apoptosis,MCF-7 cells,flowcytometry analysis.